ANALISIS PUTUSAN HAKIM TERHADAP TERSANGKA DALAM STATUS DAFTAR PENCARIAN ORANG (DPO) PASCA MELAKUKAN PRA PERADILAN - Zainudin Hasan (KEADILAN PROGRESIF, 2021)
Within the framework of upholding justice, legal certainty and the rights of suspects, lawmakers create a new institution, namely the pretrial institution. Institutions for the protection of suspects' rights and dignity, the protection of suspects gets unauthorized behavior or acts without reason based on the law. Pre-trial is the authority of the District Court to examine and decide on the legality, whether or not the arrest is legitimate or whether the investigation is terminated or the termination of the prosecution Request compensation or repair by the suspect or assistance. Then the Criminal Suspect Included in the People's Search List (DPO) in the case of filing a pretrial petition has been carried out in the Supreme Court Circular Letter (SEMA) Number 1 of 2018. concerning, pretrial for suspects who bring themselves or are in the status of the People's Search List hereinafter referred to as (DPO).